2012
DOI: 10.1007/s10753-012-9543-5
|View full text |Cite
|
Sign up to set email alerts
|

p53 Contributes to Quercetin-Induced Apoptosis in Human Rheumatoid Arthritis Fibroblast-like Synoviocytes

Abstract: In the present study, we sought to explore the mechanism of quercetin-induced apoptosis in rheumatoid arthritis fibroblast-like synoviocytes (RAFLSs). DNA fragmentation assay was used to detect quercetin-induced apoptosis in RAFLSs. The cleavages of caspase-3 and caspase-9 and the accumulation of cytosolic cytochrome C were measured by western blot in quercetin-treated RAFLSs. Mitochondrial membrane potential was tested by flow cytometry. Small interfering RNAs were used to knock down the expression of protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The antiangiogenic effect of quercetin was also demonstrated in vitro and in vivo experiments using human umbilical vein endothelial cells and chicken chorioallantoic membrane respectively [33]. Additionally, Tan WF et al [33] reported that quercetin inhibited the proliferation of NIH-3T3 fibroblast cells, while studies in RA patients revealed that quercetin induced apoptosis of fibroblast-like synoviocytes (FLS) by activating p53, reducing cytochrome c release and inhibiting Bcl-2, Bax and IL-1 [25,44]. Apoptosis induced by quercetin has also been reported in DC [43].…”
Section: Consistent With the Absence Of The Disease The Control Groumentioning
confidence: 93%
See 1 more Smart Citation
“…The antiangiogenic effect of quercetin was also demonstrated in vitro and in vivo experiments using human umbilical vein endothelial cells and chicken chorioallantoic membrane respectively [33]. Additionally, Tan WF et al [33] reported that quercetin inhibited the proliferation of NIH-3T3 fibroblast cells, while studies in RA patients revealed that quercetin induced apoptosis of fibroblast-like synoviocytes (FLS) by activating p53, reducing cytochrome c release and inhibiting Bcl-2, Bax and IL-1 [25,44]. Apoptosis induced by quercetin has also been reported in DC [43].…”
Section: Consistent With the Absence Of The Disease The Control Groumentioning
confidence: 93%
“…[16]. d) prevents angiogenesis; e) inhibits transcription factors such as NF-; f) reduces enzymes like MMPs, COX, hyaluronidases and collagenases; g) promotes apoptosis of pathogenic cells, and h) inhibits oxidative metabolism [21,[25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al (68) demonstrated that quercetin can suppress dendritic cell activation and, thus, may potentially be used for the prevention and treatment of inflammation, autoimmunity, and transplantation. Moreover, quercetin can induce apoptosis in RA fibroblast-like synoviocytes through mitochondrial pathway (188). Evidence for the possible clinical applications of quercetin is increasing.…”
Section: Antioxidant and Autoimmunitymentioning
confidence: 99%
“…Taken together, all these data suggest that resveratrol could inhibit TNF-α-induced cell proliferation and promote cell apoptosis at least partly through downregulation of Beclin-1, further inhibiting TNF-α-induced autophagy in RA-FLS.p53, a tumour-suppressor protein, plays a central role in the induction of cell cycle arrest and cell apoptosis in response to diverse cellular stimuli. Accumulating evidence has demonstrated that p53 plays a crucial role in RA-FLS cell apoptosis[3,20,32]. p53 signalling pathway has become a promising target in the treatment of RA.…”
mentioning
confidence: 99%